METODE PICTURE AND PICTURE DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU PADA SEKOLAH DASAR - I Gede Putra Ariawan (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2021)
The application of learning methods, especially at the elementary school level, requires the accuracy of the teacher in adjusting the characteristics of students by paying attention to the age level and the environment around the students. Seeing the characteristics of students at the elementary school level who have a tendency to play, so that one of the learning models that can be applied is the Picture and Picture cooperative model. The application of the Picture and Picture type of cooperative learning model can be an alternative for teachers in making variations in classroom learning so that students do not feel bored and the scores will be able to reach the set standards. Learning by using the Picture and Picture method in Hindu religious education subjects at the primary to secondary level can be applied as long as the learning can be done using picture media. Hindu religious education lessons that can use this method include learning the holy place, avatara, susila and other materials.